TKA Results Are Not Compromised By Previous Arthroscopic Procedures - Issa, Kimona; Naziri, Qais; Johnson, Aaron J.; Pivec, Robert; Bonutti, Peter M.; Mont, Michael A. (The Journal of Knee Surgery, 2012)
This study investigated whether two or more previous arthroscopic procedures had an effect on the outcomes of total knee arthroplasty (TKA). We compared 60 patients (62 knees) who had a mean age of 56 years, a mean follow-up of 39 months (range, 26 to 68 months), and a minimum of two arthroscopic procedures before their TKA with a group of patients (n = 438) who underwent TKAs without any previous knee surgery. Clinical outcome was evaluated using Knee Society objective and function scores. Implant survivorship, with revision for aseptic component failure as an end point, was 98% in both cohorts. In the postarthroscopic group, the mean Knee Society objective and function scores improved to a mean of 92 and 89 points, respectively. Radiographic analysis did not find any differences between the two groups. In conclusion, the authors did not find that earlier arthroscopic procedures negatively affected the outcome of TKA.
Keywords: total knee arthroplasty; arthroscopy; knee society objective and function scores; clinical survivorship